2012
DOI: 10.1155/2012/148403
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Inhibitory Effects of Flupirtine, a Centrally Acting Analgesic, on Delayed Rectifier K+Currents in Motor Neuron-Like Cells

Abstract: Flupirtine (Flu), a triaminopyridine derivative, is a centrally acting, non-opiate analgesic agent. In this study, effects of Flu on K+ currents were explored in two types of motor neuron-like cells. Cell exposure to Flu decreased the amplitude of delayed rectifier K+ current (I K(DR)) with a concomitant raise in current inactivation in NSC-34 neuronal cells. The dissociation constant for Flu-mediated increase of I K(DR) inactivation rate was about 9.8 μM. Neither linopirdine (10 μM), NMDA (30 μM), nor gabazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…In continued presence linopirdine, further application of 10 μM flupirtine significantly reversed linopirdine-induced inhibition of I K ( M ) in mHippoE-14 neurons ( Figure 6 ). Moreover, in continued presence of 10 μM PIO, subsequent addition of 10 μM flupirtine, an activator of I K ( M ) (Wu et al, 2012), was found to reverse its inhibition of I K ( M ) ( Figure 7 ). Therefore, it is possible that the presence of PIO suppressed the amplitude of I K ( M ) effectively in mHippoE-14 hippocampal neurons.…”
Section: Resultsmentioning
confidence: 97%
“…In continued presence linopirdine, further application of 10 μM flupirtine significantly reversed linopirdine-induced inhibition of I K ( M ) in mHippoE-14 neurons ( Figure 6 ). Moreover, in continued presence of 10 μM PIO, subsequent addition of 10 μM flupirtine, an activator of I K ( M ) (Wu et al, 2012), was found to reverse its inhibition of I K ( M ) ( Figure 7 ). Therefore, it is possible that the presence of PIO suppressed the amplitude of I K ( M ) effectively in mHippoE-14 hippocampal neurons.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated to be a suitable model for investigations on the mechanisms of neuronal development and differentiation in vitro and for studying electrophysiological properties of motor neurons in spite of being not considered as an adult motor neuron [1820]. The biophysical properties of delayed-rectifier K + current [ I K(DR) ] in NSC-34 cells were previously found to resemble the K V 3.1-encoded current because of positive mRNA detection of K V 3.1 ( KCNC1 ) [21, 22]. As NSC-34 cells were differentiated, the density of I K(DR) was significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…5). Although alterations in the steady-state activation and inactivation curves are not strictly required in state-dependent drug-channel interaction, most state-dependent channel blockers alter the steady-state channel kinetics (such as a left-shift of inactivation) (49,50). Third, when spontaneous channel activation and inactivation were prevented by holding E m at a hyperpolarized potential (À110 mV), the first depolarizing pulse after the~2-min treatment with MK801 produced an identical degree and pattern of Kv-channel inhibition as in the steady-state experiments (Fig.…”
Section: Mechanism Of Kv-channel Inhibition By Mk801mentioning
confidence: 99%
“…In the cardiovascular system, MK801 induces hypertension and tachycardia (12,13), much as ketamine does. MK801 has been reported to produce psychomotor and anesthetic effects that are almost indistinguishable from those Abbreviations: 5-HT 2A R, 5-HT 2A receptor; BAPTA, 1,2-bis(aminophenoxy) ethane-N,N,N 0 ,N 0 -tetraacetic acid; BK Ca , big conductance Ca 2þ -activated K þ ; CNS, central nervous system; E m , membrane potential; G m , membrane conductance; GPCR, G-protein coupled receptor; IeV, currentevoltage; IC 50 , half inhibition concentration; Kv channel, voltage-gated K þ channel; n, Hill coefficient; NMDAr, NMethyl-D-aspartate receptor; NT, normal Tyrode; PCP, phencyclidine; RMASMCs, rat mesenteric arterial smooth muscle cells; SD, SpragueeDawley. observed after treatment with traditional dissociative NMDArantagonist anesthetics such as PCP and ketamine.…”
Section: Introductionmentioning
confidence: 99%